Lignin / maltose composite hard carbon negative electrode material and preparation method and application thereof
Patent Information
- Application Number
- CN202611098861.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-10-13
AI Technical Summary
[0005]为解决现有技术中木质素基硬碳制备工艺复杂、能耗高,且快速焦耳热碳化难以直接处理高电阻木质素前驱体并定向构建闭孔结构的问题,本发明提供了一种木质素/麦芽糖复合硬碳负极材料及其制备方法与应用
[0020]本发明采用“预碳化-物理研磨混合-快速焦耳热碳化”三步法制备木质素/麦芽糖复合硬碳负极材料。首先将碱木质素在惰性气氛下进行预碳化处理,形成具有一定石墨化程度的导电碳骨架;然后将碱木质素衍生微孔碳基底与麦芽糖粉末通过简单的物理研磨混合,使麦芽糖均匀吸附并分散于微孔碳的孔隙表面及颗粒间隙中,完全摒弃了传统木质素与糖类复合时依赖水热反应等复杂液相工艺的束缚;最后将所得复合材料置于焦耳热碳化设备中,利用瞬时超高温与极高升温速率创造的非平衡热力学条件,使麦芽糖热解碳在孔隙内壁沉积以封堵开孔入口,同时在受限空间内产生气体压力撑开并创造新的微孔,实现闭孔结构的高效定向构建。整个制备过程工艺路线简洁、无需使用强腐蚀性活化剂或硬模板、不产生有机废液,具有显著的绿色环保优势和规模化应用潜力。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of sodium-ion battery anode materials, and particularly relates to a lignin / maltose composite hard carbon anode material, its preparation method, and its application. Background Technology
[0002] Hard carbon is a non-graphite carbon material that is difficult to graphitize and retains its disordered carbon structure even after high-temperature heat treatment. Its interlayer spacing (0.36~0.40 nm) and abundant pore structure provide an ideal environment for sodium-ion storage. The sodium storage capacity of hard carbon is contributed by both the slope region and the plateau region, with the plateau region capacity being key to improving the energy density of sodium-ion batteries. The closed-pore structure is the core source of the plateau region capacity. Therefore, constructing abundant closed-pore structures is crucial for improving the sodium storage performance of hard carbon anodes.
[0003] Lignin, as a widely available, inexpensive, and aromatic natural biomass polymer, is an ideal precursor for preparing hard carbon anode materials. However, existing preparation methods using lignin as a raw material still have significant drawbacks. In terms of processing technology, chemical activation or template methods are cumbersome, cause severe pollution, are difficult to process after treatment, and easily introduce impurities. Strategies that combine lignin with organic compounds such as sugars often rely on complex liquid-phase processes such as hydrothermal reactions, which involve many steps, are time-consuming, and energy-intensive, limiting large-scale applications. Regarding carbonization technology, existing research mostly uses traditional tubular furnace heating. The formation of closed-pore structures requires extremely high carbonization temperatures (>1300℃) and several hours of heat preservation, resulting in high energy consumption and low efficiency. Furthermore, this process relies on the spontaneous rearrangement and shrinkage of the carbon skeleton at high temperatures, which is a thermodynamically driven passive process, making it difficult to achieve directional construction and precise control of closed pores at specific defects or pores.
[0004] Rapid Joule thermal carbonization technology heats carbon sources to ultra-high temperatures within seconds to tens of seconds using instantaneous high-energy current pulses, offering advantages such as rapid heating rate, low energy consumption, and high efficiency. Existing research has confirmed that, compared to traditional slow heating, hard carbon obtained through Joule thermal carbonization exhibits smaller particle size, larger interlayer spacing, and richer closed-pore structures, demonstrating superior rate performance and low-temperature sodium storage capacity. However, this technology still faces pressing challenges: firstly, Joule thermal carbonization relies on the conductivity of the raw materials to generate heat; direct carbonization of high-resistivity precursors requires extremely high applied voltages to trigger a Joule thermal response, resulting in low energy utilization efficiency and limiting the direct application of high-resistivity biomass raw materials such as lignin; secondly, existing research primarily focuses on overall structural regulation, lacking effective technical solutions for the directional construction of specific closed pores using instantaneous high temperatures and for introducing guest components into microporous systems to synergistically optimize sodium storage sites. Summary of the Invention
[0005] To address the problems of complex and energy-intensive preparation processes for lignin-based hard carbon in existing technologies, and the difficulty in directly processing high-resistivity lignin precursors and directionally constructing closed-cell structures through rapid Joule thermal carbonization, this invention provides a lignin / maltose composite hard carbon anode material, its preparation method, and its applications.
[0006] The technical solution of this invention:
[0007] A method for preparing a lignin / maltose composite hard carbon anode material includes the following steps:
[0008] Step 1: Pre-carbonize alkali lignin under an inert atmosphere, grind the obtained pre-carbonized product, and then successively acid wash, water wash and dry to obtain alkali lignin-derived microporous carbon substrate.
[0009] Step 2: Physically grind and mix the alkali lignin-derived microporous carbon substrate with maltose powder to obtain an alkali lignin / maltose composite material.
[0010] Step 3: Place the alkali lignin / maltose composite material in a Joule heating carbonization device and perform Joule heating carbonization treatment under vacuum or inert atmosphere. After carbonization, the material is acid washed, water washed, and dried to obtain the lignin / maltose composite hard carbon anode material.
[0011] Furthermore, the pre-carbonization treatment conditions described in step one are as follows: under a nitrogen atmosphere with a flow rate of 20~25 mL / min, the temperature is increased to 250~350℃ at a heating rate of 3~5℃ / min and held for 0.5~1h, and then increased to 500~600℃ and held for 1~3h.
[0012] Furthermore, the pickling in step one involves soaking in 1 mol / L hydrochloric acid for 10 hours, and the drying is carried out under vacuum conditions of 50~70℃ and -70~-80 kPa for 12~24 hours.
[0013] Furthermore, in step two, the mass ratio of the alkali lignin-derived microporous carbon substrate to the maltose powder is 1:0.3 to 1:3.
[0014] Furthermore, the physical grinding and mixing time in step two is 15-30 minutes.
[0015] Furthermore, the Joule heating carbonization process described in step three involves heating the alkali lignin / maltose composite material to the carbonization endpoint temperature of 1000-1600℃ within 10-16 seconds at a heating rate of 50-100℃ / s, followed by cooling at a cooling rate of 50-200℃ / s.
[0016] Furthermore, the pickling in step three involves soaking in 1 mol / L hydrochloric acid for 10 hours, and the drying is carried out under vacuum conditions of 50~80℃ and -70~-80 kPa for 12~24 hours.
[0017] A lignin / maltose composite hard carbon anode material prepared by the preparation method provided by the present invention.
[0018] The application of a lignin / maltose composite hard carbon anode material provided by the present invention in the preparation of anodes for sodium-ion batteries or lithium-ion batteries.
[0019] The beneficial effects of this invention are:
[0020] This invention employs a three-step method—pre-carbonization, physical grinding and mixing, and rapid Joule thermal carbonization—to prepare lignin / maltose composite hard carbon anode materials. First, alkali lignin is pre-carbonized under an inert atmosphere to form a conductive carbon framework with a certain degree of graphitization. Then, the alkali lignin-derived microporous carbon substrate is mixed with maltose powder through simple physical grinding, allowing the maltose to be uniformly adsorbed and dispersed on the pore surface and between particles of the microporous carbon. This completely eliminates the constraints of complex liquid-phase processes such as hydrothermal reactions required in traditional lignin-sugar composites. Finally, the resulting composite material is placed in a Joule thermal carbonization device. Utilizing the non-equilibrium thermodynamic conditions created by instantaneous ultra-high temperature and extremely high heating rate, the pyrolytic carbon from the maltose deposits on the inner walls of the pores to seal the openings. Simultaneously, gas pressure generated within the confined space expands and creates new micropores, achieving efficient and directional construction of closed-pore structures. The entire preparation process is simple, requires no highly corrosive activators or hard templates, and generates no organic waste liquid, exhibiting significant green environmental advantages and potential for large-scale application.
[0021] Through the synergistic effect of the above-mentioned technical means, the lignin / maltose composite hard carbon anode material prepared by this invention forms a rich vortex-like topological closed-pore structure, increased carbon interlayer spacing, and a highly disordered carbon skeleton, effectively increasing the sodium ion storage sites and improving ion transport kinetics. Electrochemical performance tests show that the material achieves a first-cycle charging specific capacity of 335.9 mAh / g at a current density of 0.1 A / g, and a first-cycle coulombic efficiency as high as 97.95%, which are significantly improved compared to the soda ash lignin hard carbon material without maltose composite; the charge transfer resistance is significantly reduced, the sodium ion diffusion resistance is decreased, and the rate performance and long-term cycle stability are effectively improved. This indicates that this invention successfully overcomes the technical bottleneck of the difficulty in directly performing Joule heating carbonization of high resistivity lignin raw materials, and achieves a comprehensive improvement in the sodium storage performance of lignin-based hard carbon materials.
[0022] The technical solution provided by this invention opens up a completely new technical path for the green, low-energy-consumption, and high-performance preparation of lignin-based hard carbon anode materials. By ingeniously combining pre-carbonization pore-forming, physical composite, and instantaneous ultra-high temperature carbonization, it not only solves the problems of complex preparation processes, high energy consumption, and difficulty in directional construction of closed-cell structures in existing lignin-based hard carbon processes, but also provides a feasible solution for the application of rapid Joule thermal carbonization technology in the field of high-resistivity biomass precursors. This hard carbon anode material can be applied to sodium-ion batteries and can also be extended to the field of lithium-ion battery anodes, showing broad application prospects and significant industrialization value in the field of new energy storage technology. Attached Figure Description
[0023] Figure 1 X-ray diffraction patterns of the hard carbon anode material samples prepared in Examples 1-5 and Comparative Example 1;
[0024] Figure 2 TEM images of hard carbon anode material samples prepared in Comparative Example 1 and Example 4, A for Comparative Example 1 and B for Example 4;
[0025] Figure 3 SEM images of hard carbon anode material samples prepared in Comparative Example 1 and Example 4, A is Comparative Example 1, B is Example 4;
[0026] Figure 4 Comparison of Nyquist impedance curves and magnified views of two sodium-ion batteries assembled with hard carbon anode materials prepared in Comparative Example 1 and Example 4.
[0027] Figure 5 The graph shows a comparison of the first 6 cycles of constant current charge-discharge curves of two sodium-ion batteries assembled with hard carbon anode materials prepared in Comparative Example 1 and Example 4 at a current density of 0.1 A / g; A is a lignin hard carbon-based battery, and B is a composite hard carbon-based battery.
[0028] Figure 6 The graph shows a comparison of the capacity and coulombic efficiency curves of two sodium-ion batteries assembled with hard carbon anode materials prepared in Comparative Example 1 and Example 4 at a current density of 0.1 A / g after 80 cycles. A is a lignin hard carbon-based battery, and B is a composite hard carbon-based battery. Detailed Implementation
[0029] The technical solution of the present invention will be further described below with reference to embodiments, but it is not limited thereto. Any modifications or equivalent substitutions to the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be covered within the protection scope of the present invention. In the following embodiments, the process equipment or apparatus not specifically specified are all conventional equipment or apparatus in the art. Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commercially available; unless otherwise specified, the technical means used in the embodiments of the present invention are all conventional means well known to those skilled in the art.
[0030] Example 1
[0031] This embodiment provides a method for preparing a lignin / maltose composite hard carbon anode material based on rapid Joule thermal carbonization. In the raw materials, alkali lignin is an industrial byproduct obtained from the spray drying of black liquor from alkaline pulping and papermaking. It is a brown or yellow powder with a molecular weight of approximately 1000-2000, soluble in water and alkaline solutions, and is a widely available and inexpensive natural aromatic polymer. Maltose is a disaccharide composed of two glucose units linked by an α-1,4 glycosidic bond. It is a colorless or white crystal, easily soluble in water, and widely used in the food and pharmaceutical industries.
[0032] The preparation method of the lignin / maltose composite hard carbon anode material in this embodiment specifically includes the following steps:
[0033] Step 1: Preparation of alkali lignin-derived microporous carbon:
[0034] Alkali lignin raw material was dried to constant weight in a 60℃ forced-air drying oven. The dried alkali lignin was then placed in a tube furnace and pre-carbonized under a nitrogen atmosphere with a nitrogen flow rate controlled at 25 mL / min. The temperature was increased to 300℃ at a rate of 5℃ / min and held for 0.5 h, then increased to 600℃ at a rate of 5℃ / min and held for 2 h. After the holding period, the temperature was allowed to cool naturally to room temperature. The pre-carbonized product was removed and manually ground in an agate mortar for 1 h. The ground powder was immersed in 1 mol / L hydrochloric acid for 10 h for acid washing, and then repeatedly washed with deionized water until neutral. The washed product was dried in a 60℃ vacuum drying oven for 24 h with a vacuum degree controlled at -75 kPa to obtain the alkali lignin-derived microporous carbon substrate.
[0035] This step aims to remove numerous heteroatoms from alkali lignin in the form of small molecules such as H2O, CO2, and CH4, forming a stable, microporous carbon skeleton while retaining a certain amount of oxygen-containing active functional groups such as phenolic hydroxyl groups, alcoholic hydroxyl groups, carboxyl groups, and carbonyl groups. These oxygen-containing functional groups, acting as polar sites, enhance the adsorption affinity of maltose molecules on the microporous surface, promoting the uniform dispersion of maltose during physical grinding and mixing. During Joule heating carbonization, these functional groups decompose at instantaneous high temperatures to generate gas, which helps to create pressure within the confined pores, expanding and creating new microporous structures.
[0036] During the pre-carbonization process, the aromatic structure of alkali lignin undergoes condensation and rearrangement, transforming the raw material from a high-resistivity insulator into a conductive carbon skeleton with a certain degree of graphitization. This enables the material itself to have a current path and directly respond to the Joule heating effect without the need for an extremely high external driving voltage. This fundamentally overcomes the bottleneck of biomass raw materials such as lignin being difficult to directly undergo Joule heating carbonization.
[0037] Step 2: Preparation of alkali lignin / maltose composite material:
[0038] Take the maltose raw material and dry it in a 60℃ forced-air drying oven until constant weight. Mix the alkali lignin-derived microporous carbon obtained in step one with the dried maltose powder at a mass ratio of 3:1, and manually grind it in an agate mortar for 20 minutes until it is evenly mixed to obtain the alkali lignin / maltose composite material.
[0039] This step utilizes the physical adsorption of maltose molecules on the surface of alkali lignin-derived microporous carbon. Solid-phase grinding achieves uniform dispersion of guest molecules on the surface of the microporous carbon particles and at the pore inlets, eliminating the need for any solvents and completely avoiding the lengthy reaction times and subsequent solvent separation steps of traditional hydrothermal or liquid-phase impregnation processes. This simplified operation not only reduces energy consumption and equipment requirements but also eliminates the environmental burden of organic wastewater discharge, making the entire compounding process greener, more efficient, and more conducive to large-scale production.
[0040] Step 3: Preparation of alkali lignin / maltose composite hard carbon anode material:
[0041] A certain mass of alkali lignin / maltose composite material was weighed, placed in a graphite mold, and then placed in a Joule heat pipe furnace (model T2500-P5000). The furnace was evacuated to -75 kPa and heated from room temperature to 1300℃ in 13 seconds at a heating rate of 100℃ / s, followed by cooling to room temperature at a cooling rate of 100℃ / s.
[0042] The carbonized product was removed and manually ground for 1 hour using an agate mortar. The ground powder was then immersed in 1 mol / L hydrochloric acid for 10 hours for acid washing, followed by repeated washing with deionized water until neutral. The washed product was then dried in a vacuum drying oven at 60℃ for 24 hours, with the vacuum degree controlled at -75 kPa, to obtain the lignin / maltose composite hard carbon anode material.
[0043] This step utilizes the instantaneous ultra-high temperature and extremely high heating rate of rapid Joule heating carbonization to pyrolyze maltose within seconds, transforming it into a carbonaceous deposit. This deposit then deposits and reorganizes on the pore walls and surface of alkali lignin-derived microporous carbon under non-equilibrium conditions. On one hand, this carbonaceous deposit effectively seals the open pore entrances, efficiently transforming it into a closed-pore structure crucial for sodium storage, overcoming the shortcomings of traditional carbonization processes where closed-pore formation relies on thermodynamic spontaneous rearrangement and is difficult to directionally construct. On the other hand, the intense expansion and carbonization effect of maltose under instantaneous ultra-high temperature causes the rapidly released gases to generate internal pressure within the confined pores, helping to open and create new micropores, further enriching the number of closed pores. Simultaneously, the carbonaceous deposit formed by maltose pyrolysis interconnects with the original lignin carbon skeleton, forming a continuous conductive network. This avoids the problem of impaired material conductivity due to the introduction of guest components, ensuring efficient electron transport during the electrochemical reaction process.
[0044] Example 2
[0045] This embodiment provides a method for preparing a lignin / maltose composite hard carbon anode material based on rapid Joule thermal carbonization. The alkali lignin and maltose in the raw materials are the same as in Example 1.
[0046] The preparation method of the lignin / maltose composite hard carbon anode material in this embodiment specifically includes the following steps:
[0047] Step 1: Preparation of alkali lignin-derived microporous carbon:
[0048] Alkali lignin raw material was dried to constant weight in a 60℃ forced-air drying oven. The dried alkali lignin was then placed in a tube furnace and pre-carbonized under a nitrogen atmosphere with a nitrogen flow rate controlled at 25 mL / min. The temperature was increased to 300℃ at a rate of 5℃ / min and held for 0.5 h, then increased to 600℃ at a rate of 5℃ / min and held for 2 h. After the holding period, the temperature was allowed to cool naturally to room temperature. The pre-carbonized product was removed and manually ground in an agate mortar for 1 h. The ground powder was immersed in 1 mol / L hydrochloric acid for 10 h for acid washing, and then repeatedly washed with deionized water until neutral. The washed product was dried in a 60℃ vacuum drying oven for 24 h with a vacuum degree controlled at -75 kPa to obtain the alkali lignin-derived microporous carbon substrate.
[0049] Step 2: Preparation of alkali lignin / maltose composite material:
[0050] Take maltose raw material and dry it in a 60℃ forced-air drying oven until constant weight. Mix the alkali lignin-derived microporous carbon obtained in step one with the dried maltose powder at a mass ratio of 2:1, and manually grind it in an agate mortar for 20 minutes until it is evenly mixed to obtain the alkali lignin / maltose composite material.
[0051] Step 3: Preparation of alkali lignin / maltose composite hard carbon anode material:
[0052] A certain mass of alkali lignin / maltose composite material was weighed, placed in a graphite mold, and then placed in a Joule heat pipe furnace (model T2500-P5000). The furnace was evacuated to -75 kPa and heated from room temperature to 1300℃ in 13 seconds at a heating rate of 100℃ / s, followed by cooling to room temperature at a cooling rate of 100℃ / s.
[0053] The carbonized product was removed and manually ground for 1 hour using an agate mortar. The ground powder was then immersed in 1 mol / L hydrochloric acid for 10 hours for acid washing, followed by repeated washing with deionized water until neutral. The washed product was then dried in a vacuum drying oven at 60℃ for 24 hours, with the vacuum degree controlled at -75 kPa, to obtain the lignin / maltose composite hard carbon anode material.
[0054] Example 3
[0055] This embodiment provides a method for preparing a lignin / maltose composite hard carbon anode material based on rapid Joule thermal carbonization. The alkali lignin and maltose in the raw materials are the same as in Example 1.
[0056] The preparation method of the lignin / maltose composite hard carbon anode material in this embodiment specifically includes the following steps:
[0057] Step 1: Preparation of alkali lignin-derived microporous carbon:
[0058] Alkali lignin raw material was dried to constant weight in a 60℃ forced-air drying oven. The dried alkali lignin was then placed in a tube furnace and pre-carbonized under a nitrogen atmosphere with a nitrogen flow rate controlled at 25 mL / min. The temperature was increased to 300℃ at a rate of 5℃ / min and held for 0.5 h, then increased to 600℃ at a rate of 5℃ / min and held for 2 h. After the holding period, the temperature was allowed to cool naturally to room temperature. The pre-carbonized product was removed and manually ground in an agate mortar for 1 h. The ground powder was immersed in 1 mol / L hydrochloric acid for 10 h for acid washing, and then repeatedly washed with deionized water until neutral. The washed product was dried in a 60℃ vacuum drying oven for 24 h with a vacuum degree controlled at -75 kPa to obtain the alkali lignin-derived microporous carbon substrate.
[0059] Step 2: Preparation of alkali lignin / maltose composite material:
[0060] Take maltose raw material and dry it in a 60℃ forced-air drying oven until constant weight. Mix the alkali lignin-derived microporous carbon obtained in step one with the dried maltose powder at a mass ratio of 1:3, and manually grind it in an agate mortar for 20 minutes until it is evenly mixed to obtain the alkali lignin / maltose composite material.
[0061] Step 3: Preparation of alkali lignin / maltose composite hard carbon anode material:
[0062] A certain mass of alkali lignin / maltose composite material was weighed, placed in a graphite mold, and then placed in a Joule heat pipe furnace (model T2500-P5000). The furnace was evacuated to -75 kPa and heated from room temperature to 1300℃ in 13 seconds at a heating rate of 100℃ / s, followed by cooling to room temperature at a cooling rate of 100℃ / s.
[0063] The carbonized product was removed and manually ground for 1 hour using an agate mortar. The ground powder was then immersed in 1 mol / L hydrochloric acid for 10 hours for acid washing, followed by repeated washing with deionized water until neutral. The washed product was then dried in a vacuum drying oven at 60℃ for 24 hours, with the vacuum degree controlled at -75 kPa, to obtain the lignin / maltose composite hard carbon anode material.
[0064] Example 4
[0065] This embodiment provides a method for preparing a lignin / maltose composite hard carbon anode material based on rapid Joule thermal carbonization. The alkali lignin and maltose in the raw materials are the same as in Example 1.
[0066] The preparation method of the lignin / maltose composite hard carbon anode material in this embodiment specifically includes the following steps:
[0067] Step 1: Preparation of alkali lignin-derived microporous carbon:
[0068] Alkali lignin raw material was dried to constant weight in a 60℃ forced-air drying oven. The dried alkali lignin was then placed in a tube furnace and pre-carbonized under a nitrogen atmosphere with a nitrogen flow rate controlled at 25 mL / min. The temperature was increased to 300℃ at a rate of 5℃ / min and held for 0.5 h, then increased to 600℃ at a rate of 5℃ / min and held for 2 h. After the holding period, the temperature was allowed to cool naturally to room temperature. The pre-carbonized product was removed and manually ground in an agate mortar for 1 h. The ground powder was immersed in 1 mol / L hydrochloric acid for 10 h for acid washing, and then repeatedly washed with deionized water until neutral. The washed product was dried in a 60℃ vacuum drying oven for 24 h with a vacuum degree controlled at -75 kPa to obtain the alkali lignin-derived microporous carbon substrate.
[0069] Step 2: Preparation of alkali lignin / maltose composite material:
[0070] Take maltose raw material and dry it in a 60℃ forced-air drying oven until constant weight. Mix the alkali lignin-derived microporous carbon obtained in step one with the dried maltose powder at a mass ratio of 1:2, and manually grind it in an agate mortar for 20 minutes until it is evenly mixed to obtain the alkali lignin / maltose composite material.
[0071] Step 3: Preparation of alkali lignin / maltose composite hard carbon anode material:
[0072] A certain mass of alkali lignin / maltose composite material was weighed, placed in a graphite mold, and then placed in a Joule heat pipe furnace (model T2500-P5000). The furnace was evacuated to -75 kPa and heated from room temperature to 1300℃ in 13 seconds at a heating rate of 100℃ / s, followed by cooling to room temperature at a cooling rate of 100℃ / s.
[0073] The carbonized product was removed and manually ground for 1 hour using an agate mortar. The ground powder was then immersed in 1 mol / L hydrochloric acid for 10 hours for acid washing, followed by repeated washing with deionized water until neutral. The washed product was then dried in a vacuum drying oven at 60℃ for 24 hours, with the vacuum degree controlled at -75 kPa, to obtain the lignin / maltose composite hard carbon anode material.
[0074] Example 5
[0075] This embodiment provides a method for preparing a lignin / maltose composite hard carbon anode material based on rapid Joule thermal carbonization. The alkali lignin and maltose in the raw materials are the same as in Example 1.
[0076] The preparation method of the lignin / maltose composite hard carbon anode material in this embodiment specifically includes the following steps:
[0077] Step 1: Preparation of alkali lignin-derived microporous carbon:
[0078] Alkali lignin raw material was dried to constant weight in a 60℃ forced-air drying oven. The dried alkali lignin was then placed in a tube furnace and pre-carbonized under a nitrogen atmosphere with a nitrogen flow rate controlled at 25 mL / min. The temperature was increased to 300℃ at a rate of 5℃ / min and held for 0.5 h, then increased to 600℃ at a rate of 5℃ / min and held for 2 h. After the holding period, the temperature was allowed to cool naturally to room temperature. The pre-carbonized product was removed and manually ground in an agate mortar for 1 h. The ground powder was immersed in 1 mol / L hydrochloric acid for 10 h for acid washing, and then repeatedly washed with deionized water until neutral. The washed product was dried in a 60℃ vacuum drying oven for 24 h with a vacuum degree controlled at -75 kPa to obtain the alkali lignin-derived microporous carbon substrate.
[0079] Step 2: Preparation of alkali lignin / maltose composite material:
[0080] Take maltose raw material and dry it in a 60℃ forced-air drying oven until constant weight. Mix the alkali lignin-derived microporous carbon obtained in step one with the dried maltose powder at a mass ratio of 1:1, and manually grind it in an agate mortar for 20 minutes until it is evenly mixed to obtain the alkali lignin / maltose composite material.
[0081] Step 3: Preparation of alkali lignin / maltose composite hard carbon anode material:
[0082] A certain mass of alkali lignin / maltose composite material was weighed, placed in a graphite mold, and then placed in a Joule heat pipe furnace (model T2500-P5000). The furnace was evacuated to -75 kPa and heated from room temperature to 1300℃ in 13 seconds at a heating rate of 100℃ / s, followed by cooling to room temperature at a cooling rate of 100℃ / s.
[0083] The carbonized product was removed and manually ground for 1 hour using an agate mortar. The ground powder was then immersed in 1 mol / L hydrochloric acid for 10 hours for acid washing, followed by repeated washing with deionized water until neutral. The washed product was then dried in a vacuum drying oven at 60℃ for 24 hours, with the vacuum degree controlled at -75 kPa, to obtain the lignin / maltose composite hard carbon anode material.
[0084] Comparative Example 1
[0085] This comparative example provides a method for preparing a soda ash lignin hard carbon anode material, including the following steps:
[0086] Alkali lignin raw material was dried to constant weight in a 60℃ forced-air drying oven. The dried alkali lignin was then placed in a tube furnace and pre-carbonized under a nitrogen atmosphere with a nitrogen flow rate controlled at 25 mL / min. The temperature was increased to 300℃ at a rate of 5℃ / min and held for 0.5 h, then increased to 600℃ at a rate of 5℃ / min and held for 2 h. After the holding period, the temperature was allowed to cool naturally to room temperature. The pre-carbonized product was removed and manually ground in an agate mortar for 1 h. The ground powder was then immersed in 1 mol / L hydrochloric acid for 10 h for acid washing, followed by repeated washing with deionized water until neutral. The washed product was then dried in a 60℃ vacuum drying oven for 24 h under a vacuum controlled at -75 kPa to obtain the alkali lignin-derived microporous carbon substrate.
[0087] The above-mentioned alkali lignin-derived microporous carbon substrate was weighed and placed in a graphite mold, then placed in a Joule heat pipe furnace. The furnace was evacuated to -75 kPa and heated from room temperature to 1300℃ in 13 seconds at a heating rate of 100℃ / s, followed by cooling to room temperature at a cooling rate of 100℃ / s. The carbonized product was removed and manually ground for 1 hour using an agate mortar. The ground powder was then immersed in 1 mol / L hydrochloric acid for 10 hours for acid washing, followed by repeated washing with deionized water until neutral. The washed product was then dried in a 60℃ vacuum drying oven for 24 hours, with the vacuum level controlled at -75 kPa, yielding pure lignin hard carbon anode material, which served as a control sample.
[0088] The hard carbon anode material samples prepared in Examples 1-5 and Comparative Example 1 were characterized in structure, observed in morphology, and tested in electrochemical performance. The specific test methods and results are as follows.
[0089] I. Crystal Structure Analysis
[0090] The phase structure of the hard carbon anode material samples prepared in Examples 1-5 and Comparative Example 1 was analyzed using X-ray diffraction.
[0091] XRD test results are as follows Figure 1 As shown, the (002) diffraction peak of pure lignin carbon is sharp with a small half-peak width, and multiple clear narrow diffraction peaks can be observed at mid-to-high angles, proving that its aromatic carbon layers are well-stacked and have a higher degree of graphitization. After the introduction of maltose, the (002) peak of the composite hard carbon sample becomes significantly broadened and the diffraction intensity decreases, while the secondary fine diffraction peaks at mid-to-high angles gradually disappear; the low maltose content (3:1) sample only slightly changes the crystal structure, while the high maltose ratio sample shows a more prominent microcrystal fragmentation effect. These results indicate that the incorporation of maltose can reduce the size of graphite microcrystals, decrease the crystallinity of carbon materials, and introduce a large number of disordered regions and structural defects into the carbon framework.
[0092] II. Microstructure Characterization
[0093] The microstructure and closed-pore morphology of the hard carbon anode material samples prepared in Example 4 and Comparative Example 1 were observed using transmission electron microscopy (TEM); the surface morphology and particle size distribution of the samples were observed using scanning electron microscopy (SEM). The results are as follows: Figure 2 and Figure 3 As shown.
[0094] Figure 2 TEM observations showed that the hard carbon anode material prepared in Comparative Example 1 had a regular and ordered graphite layer stacking structure. After the addition of maltose, the original regular graphite layers were destroyed, and a large number of vortex-shaped carbon topologies were generated in the carbon skeleton. This structure can significantly increase the number of closed pores inside the material, provide more sodium ion storage sites, and effectively improve the reversible sodium storage capacity of the electrode.
[0095] Figure 3 SEM observation results showed that the hard carbon anode material prepared in Comparative Example 1 was in a bulk particle stacking state with a large number of through-pores distributed on the material surface. After the introduction of maltose co-pyrolysis modification, the composite hard carbon particles were more uniformly and densely arranged, the through-pores on the surface were significantly reduced, and the amorphous carbon of maltose generated by pyrolysis blocked the original pores, constructing a large number of sodium storage closed pores inside the material.
[0096] III. Electrochemical Performance Testing
[0097] The composite hard carbon prepared in Example 4 or the lignin hard carbon prepared in Comparative Example 1 was used as the active material for the negative electrode. Super P (conductive carbon black) was used as the conductive agent, and CMC (sodium carboxymethyl cellulose) was used as the binder. The hard carbon negative electrode material, Super P and CMC were weighed and ground in an agate mortar at a mass ratio of 8:1:1 for 30 minutes. An appropriate amount of deionized water was added and stirred until a uniform slurry was formed. Copper foil was selected as the current collector. The slurry was transferred to a clean copper foil and evenly coated on the surface of the copper foil using a doctor blade coater. The foil was then dried in a vacuum drying oven at 80°C for 12 hours. After cooling, the foil was cut into circular electrode sheets with a diameter of 12 mm.
[0098] The battery was assembled in an argon-filled glove box, with metallic sodium as the counter electrode, 1M NaPF6 DIGLYME (diethylene glycol dimethyl ether) solution as the electrolyte, and GF / D glass fiber as the separator. The CR2032 coin cell was then assembled to obtain a composite hard carbon-based sodium-ion battery and a lignin hard carbon-based sodium-ion battery.
[0099] (1) Electrochemical impedance spectroscopy (EIS) tests were performed on two sodium-ion batteries using a Biologic electrochemical workstation, with a frequency range of 0.01–10 Hz. 5 With an AC amplitude of 5 mV and a frequency of Hz, EIS characterization allows for in-depth analysis of the interfacial capacitance behavior and solid-phase ion diffusion kinetics of sodium-ion batteries with lignin-based hard carbon and lignin / maltose composite hard carbon anodes. The Nyquist impedance curve consists of two segments: a semicircle in the high-frequency region and a sloping straight line in the low-frequency region. The enlarged image embedded in the attached figure shows the detailed differences in the high-frequency region between the two samples: the diameter of the high-frequency semicircle corresponds to the charge transfer resistance R at the electrode interface. ct The smaller the diameter, the lower the resistance to charge transfer; the slope of the low-frequency band reflects the bulk transport capacity of sodium ions, and the larger the slope, the smaller the solid-phase diffusion resistance of sodium ions.
[0100] Test results are as follows Figure 4As shown, the high-frequency semi-circle diameter of the composite hard carbon-based sodium-ion battery is significantly smaller than that of the lignin-based hard carbon-based sodium-ion battery, indicating a substantial reduction in the charge transfer resistance Rct. Simultaneously, the slope of the oblique line in the low-frequency region is greater, indicating lower sodium-ion diffusion resistance. These results collectively confirm that the composite hard carbon prepared by co-carbonization of lignin and maltose possesses superior interfacial charge transport and sodium-ion diffusion kinetics, explaining its superior electrochemical sodium storage performance from a kinetic perspective.
[0101] (2) Constant current charge-discharge tests of two sodium-ion batteries were conducted using the Xinwei testing system, with a voltage window of 0.01~2.0 V and a current density of 0.1~10 C; the results are as follows. Figure 5 and Figure 6 As shown.
[0102] The constant current charge-discharge curves of the two sodium-ion batteries in the first 6 cycles are as follows: Figure 5 As shown, both hard carbon anode batteries exhibit the typical "slope-plateau" sodium storage characteristics of hard carbon: the sloping segment with a potential above 0.1V corresponds to the adsorption and storage behavior of sodium ions on the carbon material surface and at defect sites; the low-voltage long plateau with a potential below 0.1V corresponds to the sodium storage process of sodium ions intercalating into the closed pores inside the carbon layer. The first discharge curves of both batteries show significant irreversible capacity, mainly due to the reduction of the electrolyte on the electrode surface to form an SEI passivation film, and irreversible side reactions occurring in oxygen-containing functional groups on the carbon matrix surface. From the second cycle onwards, the charge-discharge curves of both sets of batteries highly overlap and show little voltage polarization hysteresis, indicating that after the first cycle activation, the sodium ion intercalation / deintercalation process is highly reversible, able to stably maintain charge storage capacity, and possesses potential for long-term cycle application.
[0103] A comparison of capacity data shows that: the lignin-based hard carbon sodium-ion battery has a first-cycle charging specific capacity of 291.9 mAh / g and a discharging specific capacity of 298.6 mAh / g, with a first-cycle coulombic efficiency of 97.76% and an irreversible capacity loss of 2.24%; while the composite hard carbon-based sodium-ion battery has a first-cycle charging specific capacity of 335.9 mAh / g and a discharging specific capacity of 342.9 mAh / g, with a first-cycle coulombic efficiency of 97.95% and an irreversible capacity loss of only 2.05%. The maltose-modified composite hard carbon exhibits a significantly improved reversible sodium storage capacity while slightly reducing irreversible capacity loss, resulting in superior sodium energy storage performance.
[0104] The capacity and coulombic efficiency changes of two sodium-ion batteries after 80 cycles are shown in the following curves. Figure 6As shown, the discharge capacity of lignin-based hard carbon sodium-ion batteries decays rapidly with increasing cycling, exhibiting poor long-term cycling stability. However, after introducing maltose co-pyrolysis carbonization, the capacity decay rate of the composite hard carbon-based sodium-ion battery is significantly slowed, and its cycling stability is significantly improved. These results confirm that the Joule heating rapid carbonization process can construct a stable closed-pore and vortex carbon layer topology within the lignin carbon framework. This structure effectively buffers the carbon matrix volume expansion caused by sodium ion intercalation / deintercalation, maintaining the integrity and stability of the SEI film on the electrode surface, and greatly improving the battery's cycling stability and long cycle life. This finding is corroborated by the microstructure characterization and electrochemical impedance spectroscopy results.
Claims
1. A method for preparing a lignin / maltose composite hard carbon anode material, characterized in that, Includes the following steps: Step 1: Pre-carbonize alkali lignin under an inert atmosphere, grind the obtained pre-carbonized product, and then successively acid wash, water wash and dry to obtain alkali lignin-derived microporous carbon substrate. Step 2: Physically grind and mix the alkali lignin-derived microporous carbon substrate with maltose powder to obtain an alkali lignin / maltose composite material. Step 3: Place the alkali lignin / maltose composite material in a Joule heating carbonization device and perform Joule heating carbonization treatment under vacuum or inert atmosphere. After carbonization, the material is acid washed, water washed, and dried to obtain the lignin / maltose composite hard carbon anode material.
2. The preparation method according to claim 1, characterized in that, The pre-carbonization treatment conditions described in step one are as follows: under a nitrogen atmosphere with a flow rate of 20-25 mL / min, the temperature is increased to 250-350℃ at a heating rate of 3-5℃ / min and held for 0.5-1 h, then the temperature is increased to... Keep warm for 1-3 hours.
3. The preparation method according to claim 1 or 2, characterized in that, The pickling in step one involves soaking in 1 mol / L hydrochloric acid for 10 hours, and the drying is carried out at 50~70℃ and under vacuum conditions of -70~-80 kPa for 12~24 hours.
4. The preparation method according to claim 3, characterized in that, In step two, the mass ratio of the alkali lignin-derived microporous carbon substrate to the maltose powder is 1:0.3 to 1:
3.
5. The preparation method according to claim 4, characterized in that, The physical grinding and mixing time in step two is 15~30 minutes.
6. The preparation method according to claim 5, characterized in that, The Joule heating carbonization treatment described in step three involves heating the alkali lignin / maltose composite material to the carbonization endpoint temperature of 1000–1600°C within 10–16 seconds at a heating rate of 50–100°C / s, and then immediately... Cooling rate.
7. The preparation method according to claim 6, characterized in that, The pickling in step three involves soaking in 1 mol / L hydrochloric acid for 10 hours, and the drying is carried out under vacuum conditions of 50~80℃ and -70~-80 kPa for 12~24 hours.
8. A lignin / maltose composite hard carbon anode material prepared by any one of the preparation methods described in claims 1-7.
9. The application of the lignin / maltose composite hard carbon anode material as described in claim 8 in the preparation of anodes for sodium-ion batteries or lithium-ion batteries.